Equivalent noise level response to number of vehicles: a comparison between a high traffic flow and low traffic flow highway in Klang Valley, Malaysia - Halim, Herni; Abdullah, Ramdzani (Frontiers Research Foundation, 2014)
Although much research on road traffic noise has found that noise level increase are influenced by driver behavior and source-receiver distance, little attention has been paid to the relationship between noise level and total number of vehicles on the road. In this study, 5 days measurement of noise level during peak hour and off peak hour has been carried out at two types of highways; high traffic flow highway (Sungai Besi Expressway) and low traffic flow highway (Duke Highway). Simultaneously, the number of vehicles passing the measurement point were recorded for every 15 min. Findings indicated that heavy traffic flow highway recorded higher noise level compared to low traffic flow highway. It was due to the higher number of vehicles on the heavy traffic flow highway than low traffic flow highway. Other than that, certain particular number of vehicles, noise level keeps stabilization.